If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -66 = -2x + 74 Reorder the terms: -66 + 8x = -2x + 74 Reorder the terms: -66 + 8x = 74 + -2x Solving -66 + 8x = 74 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -66 + 8x + 2x = 74 + -2x + 2x Combine like terms: 8x + 2x = 10x -66 + 10x = 74 + -2x + 2x Combine like terms: -2x + 2x = 0 -66 + 10x = 74 + 0 -66 + 10x = 74 Add '66' to each side of the equation. -66 + 66 + 10x = 74 + 66 Combine like terms: -66 + 66 = 0 0 + 10x = 74 + 66 10x = 74 + 66 Combine like terms: 74 + 66 = 140 10x = 140 Divide each side by '10'. x = 14 Simplifying x = 14
| v^2+v-53=3 | | 5(4x-4)+1=20x-19 | | -23-4x=-9x+56 | | 1-7(-1/-2) | | 2m-9n-5m+4n=0 | | 700=100+4Q | | -43+7x=29+x | | 6-(-54/7) | | 17+b=25 | | 6/7*-9 | | 16+3x= | | -46+5x=-x+56 | | y=16+3x | | 2-30/39 | | 6-(-57/7) | | 68/13-4 | | -59+2x=16-3x | | -5x+1oy=0 | | 10x+18=5x+138 | | 2x^2-12=116 | | 204/39 | | -113+5x=-9x+41 | | 6x-3=16-63 | | 3x-9=-13 | | 8Y-5=4A-3 | | 7(1)+3(2)= | | 9x-40=60+4x | | 12x^2+17x-13=-8 | | 12+32=12x-7 | | 4x+12=30-6x | | 3x+8y-5x-1y=0 | | 7d-2=14d-9 |